Currency Boards, Credibility, and Macroeconomic Behavior - Sy, Amadou (IMF Working Papers; Working Paper ;, 2000)
Currency boards operate differently from standard pegs. The former exhibit greater currency stability and lower transaction costs, inflation, and nominal interest rates, but are limited in their use of devaluation. We extend Drazen and Masson's (1994) signaling model to consider the choice between currency board arrangements and standard pegs. The model shows that currency boards' effectiveness hinges on their credibility properties and that they can improve welfare even with high unemployment persistence. By reducing expected inflation and the negative employment effect arising from expected but unrealized inflation, currency boards can produce less unemployment than peg regimes that abstain from devaluation.